PERIPHERIES OF CIVIL DISSENT: YOUTUBE’S CIVIC CULTURES AND PLURALISTIC MICROPUBLICS - McCosker, Anthony (AoIR Selected Papers of Internet Research, 2014)
This paper examines a marginal YouTube channel of civil dissidence based around anarchist principles of anti-state protest and videos of challenges to police and security personnel in public/private spaces. The channel offers a useful site for considering the emergence and trajectories of pluralistic and antagonistic micropublics. The qualitative analysis focuses on a) spaces and communicative access, b) social media practices, and c) identity and affiliation. Each of these are problematised by the pluralistic and contested nature of engagement with the channel, qualifying our understanding of the civic cultures enabled and the way micropublics emerge and endure or intensify around issues of protest.